Social Ramifications of Dowry Transaction in Muslim Marriage: An Empirical Study - Rahman, Md. Mizanur; Lieberman, Ph.D, Leslie Sue (Advances in Social Sciences Research Journal, 2019)
This paper delves into the exploration of social impacts of dowry transactions in Muslim marriages of Sylhet, Bangladesh. A cross-sectional study applying mixed methods was conducted with a sample of thirty women (N=30) who experienced dowry-related violence in their marital lives and reported it to women’s agencies for arbitration or having legal action. Each sampled woman was interviewed with a semi-structured interview questionnaire that included a list of socio-economic variables to elicit the context, patterns, types of dowry transaction and its consequences on their connubial life. Major findings indicate that the bride’s party paid dowries i.e. cash money, furniture, jewelries, land etcetera to the groom’s party before or after or during marriage ceremony hoping their bride’s conjugal happiness. But the unpaid or extra dowries were there in demand that generated many socio-familial effects - most of these are negative - which contributed to increase the incidences of spousal violence against married women in conjugal lives. Women experienced a wide range of controlling behaviors as well as physical, emotional, sexual and socioeconomic violence. Husband was the main perpetrator of violence followed by his parents, brothers, sisters and relatives. Inequitable societal attitudes towards them were used to justify violence by both women and men; and thereby, perpetuate a climate where violence-reduction interventions had a limited impact.